2, 2-Dipicolylamino substituted 2-(2′-hydroxybenzofuranyl) benzoxazole (HBBO) derivative: Towards ratiometric sensing of divalent zinc cations. (June 2021) - Pariat, Thibault; Vérité, Pauline M.; Jacquemin, Denis; Massue, Julien; Ulrich, Gilles
Abstract: A dual-emissive fluorophore, HBBODipic, exhibiting an Excited-State Intramolecular Proton Transfer (ESIPT) process is described herein. This dye incorporates an aromatic amine group on the benzofuran side which is functionalized by two picolyl moieties, enabling the observation of a dual fluorescence emission in most solvents. This attractive dual emission is related to the modulation of the pKa * by electronic substitution and has already been applied for generating panchromatic white-emission. In this contribution, we extend the applicability of these HBBO-based dual emitters to the ratiometric detection of substrates, taking advantage of the highly environment-sensitive emission profile of the dye, the E*/K* intensity ratio being strongly tunable. The presence of a dipicolylamino Zn 2+ -sensitive chelate on the HBBO π-conjugated core enables a drastic change in the emission spectra upon addition of increasing equivalents of zinc perchlorate. The E*/K* dual emission slowly shifts to a single K* band, evidencing a decrease of electron density on the benzofuranol site, owing to the chelation of the Zn 2+ cation at the dipicolylamino site. The results are rationalized using theoretical calculations. Graphical abstract: Image 1 Highlights: A dual-emissive fluorophore functionalized with a selective Zn 2+ chelate exhibiting an Excited-State Intramolecular Proton Transfer (ESIPT) process is described. Its full photophysical characterization in solution and in the solid-state is described and a dual emission is observed in most environments. Addition of Zn 2+ leads to a gradual modification of the intensity ratio between the two bands paving the way to the ratiometric detection of substrates using dual-emissive ESIPT emitters. Theoretical calculations rationalized the coordination of Zn 2+ and the observation of a transient species.